This equation is separable:
d<em>y</em>/d<em>x</em> = (<em>x</em> + 5) / <em>y</em> → <em>y</em> d<em>y</em> = (<em>x</em> + 5) d<em>x</em>
Integrate both sides to get
1/2 <em>y</em>² = 1/2 (<em>x</em> + 5)² + <em>C</em> … … … (if you substitute <em>u</em> = <em>x</em> + 5)
<u>or</u>
1/2 <em>y</em>² = 1/2 <em>x</em>² + 5<em>x</em> + <em>C</em> … … … (if you integrate term-by-term)
Given that <em>y</em> (-4) = -6, meaning <em>x</em> = -4 and <em>y</em> = -6, plug this in to solve for <em>C</em>. Note that whichever method you choose determines the particular value of <em>C</em>.
1/2 (-6)² = 1/2 (-4 + 5)² + <em>C</em>
18 = 1/2 + <em>C</em>
<em>C</em> = 35/2
→ 1/2 <em>y</em>² = 1/2 (<em>x</em> + 5)² + 35/2
<u>or</u>
1/2 (-6)² = 1/2 (-4)² + 5(-4) + <em>C</em>
18 = 8 - 20 + <em>C</em>
<em>C</em> = 30
→ 1/2 <em>y</em>² = 1/2 <em>x</em>² + 5<em>x</em> + 30
Both implicit solutions are correct and equivalent; the second one is just the expanded form of the first.
If you want an explicit solution, you can solve for <em>y</em>. But keep in mind that the initial condition tells you <em>y</em> < 0, so you should take the negative square root.
1/2 <em>y</em>² = 1/2 (<em>x</em> + 5)² + 35/2
<em>y</em>² = (<em>x</em> + 5)² + 35
<em>y</em> = -√((<em>x</em> + 5)² + 35)
<u>or</u>
<em>y</em> = -√(<em>x</em>² + 10<em>x</em> + 60)